The impact of managerial competence on corporate carbon performance: An empirical study based on Chinese heavy polluters - Zhao, Zexia; Wang, Peiqiong (Frontiers in Energy Research, 2023)
Climate risk to human survival and progress can no longer be disregarded, nor can the reduction of carbon emissions be postponed. How can economic progress and carbon emission reduction be reconciled? This research studied the relationship between managerial skill and carbon emission performance. We used the Shanghai and Shenzhen A-shares data of Chinese heavy polluters from 2014 to 2019 to assess the impact of managerial competency on business carbon emission performance using a temporal and individual fixed effects model. We discovered that management competency can greatly contribute to the enhancement of carbon emission performance inside corporations. The stepwise regression technique was then utilized to examine the mediating influence of financing limitations and financial status. This study validated the threshold effect of internal pay equity among corporate managers using a threshold regression model.